The organization of enviroment protection in Lithuanian SSR schools - Šapokienė, E. (Psichologija, 1966)
The article analyzes the situation in Lithuanian SSR schools in the field of environment protection, based on 7th grade student knowledge and practical activity in 9 schools in the republic. It is described how 50 schools organized various massive tools in order to educate the appreciation for nature. The data was acquired by questionnaires in 19-63-1964. The goal of this article is to help the biology teachers to convey the environment protection knowledge more effectively.The analysis showed that student knowledge on environment protection is poor. The students know least about fostered natural flora in Lithuania and rare plants that are protected by the laws. The students also know very little about the examples of acclimatization and nature reserves. About 44.9% of the students do not know anything about the importance of the protective forest lines. That is, lessons, as the major form of teaching, are not used efficiently in order to convey the knowledge about environment protection.In practice, most of the students take part in fostering the animals – 92.5% and planting the trees – 84%. The students take very little part in fighting against plant illnesses and parasites – 5.9%. It is concluded that practical activity as well as the knowledge are better on animals than on plants. Therefore it is important to consider this.
Keywords: environment protection; knowledge on environment protection